Yazidi Genocide (Accountability and Prevention) - Alawi, Ghofran (Journal of Legal Sciences, 2026)
Genocide is known as the "crime of crimes" because of its severity. It targets entire groups and has catastrophic consequences for humanity and human dignity. On august 3,2014, ISIS terrorist gangs launched a devastating attack on the yazidi community in sinjar, northwest Iraq. ISIS carried out mass executions and forcibly transferred thousands of yazidi captives to syria. yazidi boys as young as seven were trained for combat roles and suicide missions. ISIS also subjected yazidi women and girls to enslavement, torture, inhumane treatment, murder, and rape as part of their genocidal campaign. On its eleventh anniversary, this crime continues to raise fundamental questions about the devastating consequences of inadequate protection and impunity. it underscores the urgent need for justice and collective action to prevent the recurrence of such atrocities by identifying and monitoring risk factors, recognizing early warning signs of genocide, and prosecuting ISIS for genocide local and international communities have recognized to some extent the urgent need to assist the yazidis in their recovery, however, significant efforts are still required to ensure the long-term peace and well- being of this group. Accordingly, this research presents a definition of genocide in the first section, while the second section will outline the mechanisms available for holding ISIS accountable for genocide and ways to prevent the crime.